The Blended Roles of Professional and Academic Staff in Universities of Technology: Are We Getting It Right? - Leigh Meyers; Tigamberry Naidoo; Jane Skinner (African Journal of Inter-Multidisciplinary Studies)
Tensions between academic and professional staff are still experienced in universities of technology. The article focuses on the mobility and shifting boundaries which appear to be developing in regard to this working relationship at one South African university of technology. The mixed-methods exploratory research involved data gathered in 2018 and in 2021 from both academic and professional staff. The data included findings from staff whose work spans both roles and those who have moved from one role to the other. Findings indicate that professional staff are often drawn into performing teaching and research functions, and yet experience barriers which impede their academic progress. The article argues for more overt recognition and facilitation of this blending of roles, which would seem to be particularly appropriate for universities of technology. No current literature exists on this phenomenon in South African Universities of Technology and this article hopes to fill this gap and initiate this conversation.